1997
DOI: 10.1002/pro.5560060515
|View full text |Cite
|
Sign up to set email alerts
|

Energy profile of maltooligosaccharide permeation through maltoporin as derived from the structure and from a statistical analysis of saccharide‐protein interactions

Abstract: The crystal structure of the maltodextrin-specific porin from Salmonella typhimurium ligated with a maltotrioside at the pore eyelet is known at 2.4 8, resolution. The three glucose units assume a conformation close to the natural amylose helix. The pore eyelet fits exactly the cross-section of a maltooligosaccharide chain and thus functions as a constraining orifice. The oligomer permeates the membrane by screwing along the amylose helix through this orifice. Because each glucose glides along the given helix,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 21 publications
(13 reference statements)
1
53
1
1
Order By: Relevance
“…Among them, Tyr100 and Phe259 stack to pyranose rings. The others are rather far apart from the pyranoses and appear to form an extended area of intermediate binding strength, in which the pyranoses can move [43]. Of particular significance appears to be a guideway for the A-glucan chain between Tyr89 and Tyr195, near subsites 3′ and 4′, and a second guideway between Phe183 and Tyr195, along which the protein-bound linear Aglucan can reach subsite 1 for cyclization.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, Tyr100 and Phe259 stack to pyranose rings. The others are rather far apart from the pyranoses and appear to form an extended area of intermediate binding strength, in which the pyranoses can move [43]. Of particular significance appears to be a guideway for the A-glucan chain between Tyr89 and Tyr195, near subsites 3′ and 4′, and a second guideway between Phe183 and Tyr195, along which the protein-bound linear Aglucan can reach subsite 1 for cyclization.…”
Section: Resultsmentioning
confidence: 99%
“…This permeation type involves significant energy steps only on initial association and final dissociation of the channel. Furthermore, no significant rearrangements leading to energy reorganization had to occur along the translocation pathway of a sugar molecule (30,31). This suggests that maltoporin can reduce the onset activation barrier by having its affinity site prearranged with an hydrophobic environment and a charge FIG.…”
mentioning
confidence: 95%
“…Structural considerations showed that the periodic energy profiles of the hydrogen bonds and hydrophobic contacts are shown to be shifted resulting in a "smooth" total energy profile (30). This permeation type involves significant energy steps only on initial association and final dissociation of the channel.…”
mentioning
confidence: 97%
“…Multiple H bonds are formed between the sugar hydroxyl groups and the charged residues of the two ionic tracks. Constant breaking and remaking of these hydrogen bonds has been suggested to allow movement of the substrate through the channel (8,9). The role of the greasy slide in sugar translocation through the channel will be discussed in a future paper.…”
mentioning
confidence: 99%